An experimental investigation and kinetic-modeling study of the phase transformation behavior of glycine in various carboxylic acids - SAYAN, PERVİZ; POLAT, SEVGİ (WILEY, 2019)
In this study, the phase transformation behavior from beta-glycine (Gly) to alpha-Gly was examined in the presence of three different carboxylic acid additives (acetic, tartaric, and citric acid) at three different concentrations. Initially, the structure, morphology, shape parameters, surface functional groups, and elemental properties of the crystals prepared from the additive-containing and nonadditive media were investigated. The characterization results showed that when compared with the pure medium, both the duration of the phase transformation and physicochemical properties of the alpha-Gly crystals were altered in the presence of the three carboxylic acid additives studied. Subsequently, the experimental data obtained from the thermogravimetric analysis of the alpha-Gly samples obtained from the additive containing and nonadditive media were modeled using a simplified DAEM kinetic model. On the basis of the data obtained from the distributed activation energy model, the average activation energy for the Gly crystals obtained from the pure medium was calculated to be 90.8 kJ/mol. The value for the crystals obtained from the acetic acid-containing medium was 104.0 higher than that found for the crystals from the pure medium and other two other additives studied. Besides kinetic analysis, thermogravimetric analysis/Fourier-transform infrared spectroscopy and elemental analysis confirmed that the carboxylic acid was adsorbed on the crystal's surface. The amount of acetic, tartaric, and citric acid adsorbed was 2.97, 2.38, and 1.72 mg/g, respectively.
Keywords: carboxylic acid; DAEM method; glycine; kinetics; morphology; CRYSTAL-STRUCTURE; CRYSTALLIZATION; POLYMORPHISM